2023
DOI: 10.1111/mec.16840
|View full text |Cite
|
Sign up to set email alerts
|

Sardines at a junction: Seascape genomics reveals ecological and oceanographic drivers of variation in the NW Mediterranean Sea

Abstract: By evaluating genetic variation across the entire genome, one can address existing questions in a novel way while raising new ones. The latter include how different local environments influence adaptive and neutral genomic variation within and among populations, providing insights into local adaptation of natural populations and their responses to global change. Here, under a seascape genomic approach, ddRAD data of 4609 SNPs from 398 sardines (Sardina pilchardus) collected in 11 Mediterranean and one Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 152 publications
(237 reference statements)
0
5
0
Order By: Relevance
“…Li et al, 2017; Manel, Schwartz, Luikart, & Taberlet, 2003). Spatially complex landscapes have features that might constrain gene flow, increasing population genetic structure of inhabitants compared to more homogeneous landscapes (Rahbek et al, 2019; Wang & Singh, 2019) and also harbor substantial abiotic variation that could drive local adaptation in populations from dissimilar environments (Andrews et al, 2022; Antoniou et al, 2023; Capblancq, Fitzpatrick, Bay, Exposito-Alonso, & Keller, 2020; Heraghty, Rahman, Jackson, & Lozier, 2022). Genomic data can be used to understand current and historical population structure as well as genome- environment associations that might signal local adaptation and can thus provide multiple types of information about evolutionary responses to complex landscapes in widespread species.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, 2017; Manel, Schwartz, Luikart, & Taberlet, 2003). Spatially complex landscapes have features that might constrain gene flow, increasing population genetic structure of inhabitants compared to more homogeneous landscapes (Rahbek et al, 2019; Wang & Singh, 2019) and also harbor substantial abiotic variation that could drive local adaptation in populations from dissimilar environments (Andrews et al, 2022; Antoniou et al, 2023; Capblancq, Fitzpatrick, Bay, Exposito-Alonso, & Keller, 2020; Heraghty, Rahman, Jackson, & Lozier, 2022). Genomic data can be used to understand current and historical population structure as well as genome- environment associations that might signal local adaptation and can thus provide multiple types of information about evolutionary responses to complex landscapes in widespread species.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of spatial and environmental heterogeneity across a species range can have important effects on gene flow and population structure (Li et al, 2017; Manel et al, 2003). Spatially complex landscapes have features that might constrain gene flow, increasing population genetic structure of inhabitants compared with more homogeneous landscapes (Rahbek et al, 2019; Wang & Singh, 2019) and also harbour substantial abiotic variation that could drive local adaptation in populations from dissimilar environments (Andrews et al, 2022; Antoniou et al, 2023; Capblancq, Fitzpatrick, et al, 2020; Heraghty et al, 2022). Genomic data can be used to understand current and historical population structure as well as genome–environment associations that might signal local adaptation and can thus provide multiple types of information about evolutionary responses to complex landscapes in widespread species.…”
Section: Introductionmentioning
confidence: 99%
“…Functional annotation analyses of the environment-associated RAD loci revealed that the gene sets linked to these loci play a key role in biological processes associated with environmental pressures. The retrieved top GO categories (e.g., cellular process, developmental process, metabolism, biological regulation, and response to stimulus) have been reported in other studies that measure transcriptomic responses under experimentally induced heat stress [165,166], ocean acidification [167,168], biomineralisation, energy metabolism, and heat, disease, or hypoxia tolerance [40,169]. Moreover, the gene sets reported in the present study were enrichment in four functional pathways, which included the WNT-, MAPK-, RIG-I-like receptor and Hedgehog signalling pathways and Glycerophospholipid metabolism.…”
Section: The Genomic Profile Of Environmentally-associated Rad Locimentioning
confidence: 86%
“…Indeed, the abiotic environment acts as a selective force on natural populations, shaping and maintaining variation in heritable traits (morphology, physiology, and behaviour) that provide significantly greater fitness in their local environment (i.e., local adaptation) when compared to populations from other environments [34][35][36][37]. Understanding the extent and scale of local adaptation is critical in determining how quickly and to what extent specific populations will respond to habitat changes, climate change, fisheries-or farming-induced evolution and interactions with a hatchery-or captive-reared counterparts [36,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%